Sifat Keherediteran Aljabar Lintasan dan Aljabar Lintasan Leavitt - Kariman, Delsi; Junios, Junios (Journal of Mathematics, Computations and Statistics, 2022)
This article deals with two topics, namely the hereditary property of path algebras and the hereditary property of Leavitt path algebras. The hereditary property is advantageous in studying projective modules over algebras. In the first topic, the path algebras are hereditary if the graph is finite, connected, and acyclic. In the second topic, Leavitt path algebras are hereditary if the graph is finite